Pengkajian Efektivitas Pelayanan Angkutan Penyeberangan Perintis Di Provins! Sulawesi Tengah - Rahayu, Siti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Govennent provides subsidy fur public transport operator to provide pioneers public transport service,hmrever this pravision should be evaluated yearly.The £!lJaluation is about the impravment of the services bec:ause this problem is related to govermentfinandng . There is two kind of pioneer femJ , the first ane is seroing intercity and interpravince(AKAP) and the second ane is seroing intercity in a province (AKDP).Aim of this stu.dtj is to know the constrains of ferry operational in seroing the customers in order togain improvement of the service in the future.Through research and observation in the realita and also from SISTRANAS approach, then thepioneer ferry transport with Luwuk-Salakan-Banggai route is effectively to operated only fur vehicleswith 4 and more wheels and it is inefficient fur human transport. For Ampana- Wakai-Gorontaloroute is effective and efficient both fur human and goads transport.Key words: Pioneer ferry transport.